2015
DOI: 10.1177/0004867415589794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Canterbury earthquakes on prescribing for mental health

Abstract: Short-term increases in dispensing were only observed for the classes of anxiolytics and sedatives/hypnotics. No sustained changes in dispensing occurred. These findings suggest that long-term detrimental effects on the mental health of the Canterbury population were either not present or have not resulted in increased prescribing of psychotropic medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 30 publications
5
20
1
9
Order By: Relevance
“…Another study by Beaglehole al. also did not identify any significant change in the prescription rate of anxiolytics or sedatives/ hypnotics after the Canterbury earthquakes, but did observe a shortterm increase in these medication prescriptions at 1 month after the most devastating earthquake (Beaglehole et al, 2015). Our results are similar to the above-mentioned studies; however, we do not have a clear explanation for the overall decrease in anxiolytic prescriptions or lack of change in sedative/hypnotic prescriptions after the disaster.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Another study by Beaglehole al. also did not identify any significant change in the prescription rate of anxiolytics or sedatives/ hypnotics after the Canterbury earthquakes, but did observe a shortterm increase in these medication prescriptions at 1 month after the most devastating earthquake (Beaglehole et al, 2015). Our results are similar to the above-mentioned studies; however, we do not have a clear explanation for the overall decrease in anxiolytic prescriptions or lack of change in sedative/hypnotic prescriptions after the disaster.…”
Section: Discussionsupporting
confidence: 76%
“…With regard to the short-term effects of the disaster, we similarly did not identify any significant differences in psychotropic medication prescription rates between Ansan Danwon and Cheonan city after the disaster. Yet, Beaglehole et al reported short-term increases in the use of anxiolytics and sedatives/hypnotics 1 month after a devastating earthquake (Beaglehole et al, 2015), and Trifiro et al similarly indicated increases in the prescription rates of antidepressants and antipsychotics 2 months after an earthquake (Trifiro et al, 2013). We do not have a clear explanation as to why we only observed a significant increase in antidepressant and antipsychotic prescriptions in the affected community in the long term rather than in the short term after the disaster.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This means we have been able to distinguish earthquake specific effects from other long‐term trends. These results mirror our previous study examining dispensing of psychiatric medication for all age groups . This study also reported short‐term increases in dispensing of anxiolytics and sedative/hypnotics but did not discern longer‐term effects for dispensing of antidepressants, antipsychotics, or anxiolytics.…”
Section: Discussionsupporting
confidence: 85%
“…We have previously examined dispensing of psychiatric medication to clarify the impact of the Canterbury earthquakes on the overall population. This study reported short‐term increases in anxiolytics and sedative/hypnotics, but no long‐term effects for anxiolytics, sedative/hypnotics, antidepressants, or antipsychotics as a result of the earthquake sequence. However, the possibility of differential effects for older persons was not considered in the initial study design.…”
Section: Introductionmentioning
confidence: 54%